Life cycle assessment study of solar PV systems: An example of a 2.7kWp distributed solar PV system in Singapore - Kannan, Ramachandran; Leong, Kai Choong; Osman, Ramli; Ho, Hiang Kwee; Tso, Chih Ping (Elsevier, 2006)
In life cycle assessment (LCA) of solar PV systems, energy pay back time (EPBT) is the commonly used indicator to justify its primary energy use. However, EPBT is a function of competing energy sources with which electricity from solar PV is compared, and amount of electricity generated from the solar PV system which varies with local irradiation and ambient conditions. Therefore, it is more appropriate to use site-specific EPBT for major decision-making in power generation planning. LCA and life cycle cost analysis are performed for a distributed 2.7 kW(p) grid-connected monocrystalline solar PV system operating in Singapore. This paper presents various EPBT analyses of the solar PV system with reference to a fuel oil-fired steam turbine and their greenhouse gas (GHG) emissions and costs are also compared. The study reveals that GHG emission from electricity generation from the solar PV system is less than one-fourth that from an oil-fired steam turbine plant and one-half that from a gas-fired combined cycle plant. However, the cost of electricity is about five to seven times higher than that from the oil or gas fired power plant. The environmental uncertainties of the solar PV system are also critically reviewed and presented. (C) 2005 Elsevier Ltd. All rights reserved.